Control interno sobre los ingresos del Gad Municipal del cantón Vinces - Vito Aguirre, Génesis Tibizai (2020)
The Municipal GAD of Cantón Vinces is an autonomous, administrative and financial public institution, is in charge of planning, managing and executing its own resources with the aim of solving the needs requested by citizens for public works, carrying out capacities assigned by COOTAD and the Constitution that promotes territorial growth for the change of good living. The case study has been carried out according to the subline of INVESTIGATION: MANAGEMENT OF ACCOUNTING INFORMATION, with the theme: INTERNAL CONTROL OVER THE INCOME OF THE MUNICIPAL GAD OF THE CANTÓN VINCES, was carried out by the descriptive research method, to have knowledge of the inconsistencies that exists within the entity, an interview was conducted with the person in charge of the entity's budget, information was obtained on the problem that exists in self-management income, non-compliance with tax payment by taxpayers, since they are of utmost importance because they are part of the budget. The Municipal GAD of Cantón Vinces does not have a contingency plan that motivates and makes the taxpayer aware that they must make the tax payments because due to these revenues they can finance public works.